Experiences of health informers working with intercultural communication in Stockholm, Sweden during COVID-19: a qualitative study - Eklund, Silja Mattadóttir; Bäärnhielm, Sofie; Al-Ammari, Baidar; Abshir, Hamdiya; Strand, Mattias; Cetrez, Önver A.; Puthoopparambil, Soorej Jose (Frontiers in Communication, 2025)
BackgroundDuring the initial period of the COVID-19 pandemic, it was noted that migrants in Stockholm, Sweden, had a higher risk of contracting the virus and had a higher risk of mortality. In response to this, to provide information to people who did not have Swedish as their native language and therefore had limited access to the latest information and guidelines due to potential language barriers, authorities implemented an intercultural communication response. One of the aspects of this response was to employ health informers who spoke different languages and station them in multicultural areas to provide information about COVID-19. This study explores the experiences of the health informers working with intercultural health communication during the COVID-19 response in Stockholm, Sweden.MethodsData was collected through semi-structured interviews, nine individual and four group interviews, with 23 participants. The data was collected between February and September 2022.ResultsThe findings of this study give an understanding of how health informers experienced their on-the-ground work of communicating and disseminating COVID-19 information to migrants in Stockholm. The main themes that were developed included navigating information dissemination amongst multiple information sources and narratives, the personal connection created by the health informers, and the challenging but rewarding work environment. The findings highlighted that speaking the same language and building trust through personal conversations, drawing from own experiences, and relatability were important aspects of communicating health information.ConclusionIn conclusion, this study gives a better understanding of the experience of the communication effort implemented by Region Stockholm to reach non-native Swedish speakers from the perspective of the health informers. Overall, the health informers experienced that they had an important role during the pandemic, and that they had a positive impact on the community.